Effect of Accelerated Carbonation Curing on Strength and Durability Properties of GGBS Concrete - Singh, Harvir (My University, 2018)
The effect of Accelerated Carbonation curing (ACC) was studied on the strength and durability properties of concrete containing varying percentages of Ground Granulated Blast furnace Slag (GGBS) (0% to 60%) as a partial replacement of cement. Strength property included compressive strength while the durability properties included water absorption, chloride permeability, sorptivity and acid resistance. Microstructure of the concrete specimens containing 0% and 40% GGBS was studied through SEM and XRD analysis. Specimens were cured under two types of curing regimes. One set of specimens were water cured while the other set of specimens were carbonation cured for 12 hours then they were placed in water till the age of 3 days and after that they were placed in sealed plastic bags till the testing age. From the experiments it was found that although the early carbonation improved the strength of the concrete the strength gain was not noticeable at the later ages. The carbonated specimens showed lesser water absorption at the ages of 1 day, 3 days and 28 days. Carbonated specimens exhibited lesser sorptivity value, more resistance to chloride permeability and acid attack when compared to the water cured samples. Addition of GGBS resulted in improved strength and lesser value of water absorption while 40% replacement was determined to be optimum. The GGBS concrete also exhibited lesser sorptivity value and more resistance to chloride permeability and acid attack when compared to the control mix. Microstructure analysis of the concrete samples showed the presence calcium carbonate (CaCO3) in place of calcium hydroxide (Ca(OH)2) in carbonated concrete which provided strength to the concrete. A denser microstructure was observed in concrete containing 40% GGBS when compared to the control mix.
Master of Engineering- Structural
Keywords: Accelerated Carbonation Curing; GGBS; Compressive Strength; Durability; Microstructure